The sporting resilience model: A systematic review of resilience in sport performers - Gupta, Sahen; McCarthy, Paul Joseph (Frontiers in Psychology, 2022)
We systematically reviewed resilience research in sport and exercise psychology. Sample included 92 studies comprising empirical qualitative and quantitative studies, mixed-method studies, review studies and conceptual/theoretical studies on psychological resilience in sports context. From the findings, we synthesised an evidence-based sport-specific definition and meta-model of ‘Sporting Resilience’. The review incorporates evidence from multiple culture contexts and evidence synthesised into the propositional definition and meta-model to achieve its aim. Conceptual detail and testability of the operational definition is provided. Sporting resilience provides a guiding framework for research and applied practice in a testable, objective manner. The new theoretical meta-model of resilience is derived from systematic evidence from sport psychology with theoretical considerations from positive and clinical psychology allowing generalizability. This original theory posits that there is a resilience filter comprised of biopsychosocial protective factors. The strength of this filter determines the impact of adversity and establishes the trajectory of positive adaptation. The findings of the review are used to discuss potential avenues of future research for psychological resilience in sports psychology.